Effect of pilot fuel injection timing on the performance, combustion, and exhaust emissions of biodiesel–ethanol–diethyl ether blend fueled CRDI engine under hydrogen dual fuel strategies. Issue 4 (23rd November 2021) - Bhowmik, Subrata; Paul, Abhishek; Panua, Rajsekhar
Abstract: The present investigation utilizes a completely biodiesel based ternary blend pilot fuel for the hydrogen dual fuel operation in a CRDI engine. The pilot fuel was formulated with 88% biodiesel, 10% ethanol, and 2% diethyl ether to closely replicate the cetane index and heating value of petroleum diesel. The pilot injection angle was varied at 8°, 12°, 14°, 16°, and 18° before top dead center at 210 bar fuel injection pressure to study the effect of pilot fuel injection angle on performance, combustion, and emission of a hydrogen dual fuel engine at full load condition. Three different hydrogen injection durations, 1200, 2500, and 3700 μs with a constant flow rate of 0.9 kg/h were used to assess the effect of increasing hydrogen mass flow rate on the engine. The results showed that advancing pilot fuel injection angle remarkably improved the performance of engine with 13.36% higher brake thermal efficiency, 9.28% lower hydrocarbon and 11.03% lower carbon monoxide emission with hydrogen injection duration of 3700 μs and pilot injection angle of 16° bTDC. However, this also increased the oxides of nitrogen emissions by 11.07%. Therefore, the results proved the efficacy of injection advancement of biodiesel based ternary blend pilot fuel in extracting better performance output from a hydrogen dual fuel CRDI engine.